2019
DOI: 10.2754/avb201988020249
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of stress in laboratory rabbits used for teaching purposes

Abstract: This study was intended as a contribution to the argument about possible suffering of animals used for demonstrative purposes during teaching at universities. Pharmacology lectures at the University of Veterinary and Pharmaceutical Sciences Brno, Czech Republic were selected for this experiment. The study focused on stress assessment using haematological and biochemical indices. Blood samples were drawn from 20 rabbits (Oryctolagus cuniculus f. domesticus L.) 10 days after arrival at the institute (before the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…A study model of the uterus duplex in the rabbit is, in our opinion, suitable for examining other preparations. Besides macroscopic observation, the monitoring of biochemical and haematological indices, and their subsequent inclusion in the results is also advisable (Pecin et al 2017;Urbanová et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A study model of the uterus duplex in the rabbit is, in our opinion, suitable for examining other preparations. Besides macroscopic observation, the monitoring of biochemical and haematological indices, and their subsequent inclusion in the results is also advisable (Pecin et al 2017;Urbanová et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Stress has commonly been measured not only by cortisol levels in blood but also as cortisol metabolites in feces, hair, and urine [1]. Neutrophil-lymphocyte ratio has been employed as a stress measurement as well [2], because the duration of stress affects leucocyte populations [3]. However, a major issue for animal welfare is that these techniques involve invasive procedures which may themselves cause a stress response and therefore affect the measurement of interest [4].…”
Section: Introductionmentioning
confidence: 99%
“…In pigs, no study of this type has been published yet. Only one similar study has been carried out so far by Urbanova et al (2019), focusing on stress in rabbits which showed that animals can get used to repeated manipulation; with each subsequent manipulation there was a lower hormonal stress response.…”
mentioning
confidence: 99%